Angina de Ludwig: Análisis de 11 casos - José Manuel Díaz Fernández; Isidoro Gutiérrez Macías (Editorial Ciencias Médicas, 1996)
It is about a longitudinal study on clinical, bacteriological, and therapeutic aspects of Ludwig's angina, conducted at the Maxillofacial Surgery Department of the "Saturnino Lora" Provincial Teaching Hospital from 1986 to 1990. It is concluded that this disease may be uncommom due to its inadequate diagnosis, which requires an early attention to avoid those complications apperaring generally. The treatment is mostly medical, and it is based on the association of antibiotics.